Review on VCO based ADC in modern deep submicron CMOS technology - Hor, Hon Cheong (2013)
The continuous scaling in CMOS technology has driven researchers to look for new ADC architecture that can work well in lower supply voltage and smaller device dimension. VCO-based ADCs have emerged as an attractive solution due to its highly digital intensive circuit architecture, inherent noise shaping characteristic, as well as anti-aliasing property. However, the nonlinear behavior of VCO's voltage-to-frequency characteristic has severe limitation on the performance of VCO-based ADC. This paper presents recent development in VCO-based ADC with different VCO nonlinearity suppression techniques. The advantage and disadvantage of each of these techniques will be reviewed.